The novel by H.C.Andersen "Only a Fiddler": poetics and context - Мацапура, Валентина Ивановна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The target of research in this entry is one of five novels by H.C.Andersen – “Only a Fiddler” (1837). In respect that this novel is understudied, the author of the article has brought into focus the peculiarities of its problematics and poetics, in particular, the mastery of creating character sketches, the development of the action, the role of epigraphs, examples of intermediality and intertextuality. One of the conclusions of the article is the following: all the images, described in the novel, are related to philosophical problematics of the piece of writing and to the perennial problem of the fight between good and evil.